Conditions and methods of implementation of inclusive education in Uzbekistan. (Zien Journal of Social Sciences and Humanities, 2023)
The purpose of the proposed article is to analyze the process of implementing inclusive education, the problem of creating opportunities for access to education, improving the provision of inclusive education coverage, creating an educational and methodological base for teachers, parents and the public, creating conditions for further correctional and rehabilitation work. Taking into account the priorities and shortcomings of inclusive education in the republic, the article provides an extensive development of the process of creating barrier-free conditions for disabled children, the teacher's work process, psychological, pedagogical organizational and methodological approaches in the organization of the educational process: the organization of joint work of families, schools, teachers.